HIV among female sex workers in the Central Asian Republics, Afghanistan, and Mongolia: Contexts and convergence with drug use - Baral, Stefan; Todd, Catherine S.; Aumakhan, Bulbul; Lloyd, Jennifer; Delegchoimbol, Altanchimeg; Sabin, Keith (Drug and alcohol dependence, 2013)
Central Asia is culturally and demographically diverse, both between and within its respective countries. That diversity is represented in the range of individual, network, community, and structural risks for female sex workers (FSWs) regionally. FSWs have several risk factors for HIV acquisition and transmission including behavioral, biological, and structural risk factors. Across Central Asia, sexual risks have become conflated with risks associated with injection and non-injection illicit drug use. Peer-reviewed literature databases and gray literature were searched for articles on sex work in Central Asia. The medial subject heading (MeSH) of “sex work” was cross-referenced with terms associated with Uzbekistan, Tajikistan, Turkmenistan, Kazakhstan, Kyrgyzstan, Mongolia, and Afghanistan. HIV prevalence data for FSWs suggest sustained or increasing prevalence in the region. There are increasing data directly linking HIV among FSWs to injection drug use; odds of HIV are up to 20 times higher among FSWs reporting injecting drug use. Though injecting drug use among FSWs is rare in some settings, recreational drugs and alcohol use limits other risk reduction behaviors, such as condom use. The Central Asian HIV epidemic has traditionally been assumed to be driven nearly exclusively by drug use, resulting in surveillance systems focused on parenteral transmission. The reviewed data highlight limited attention to characterizing the burden of HIV and risk factors for HIV acquisition and transmission among FSWs who use drugs. Moving forward will require enhanced HIV surveillance and research to inform HIV prevention approaches to address all levels of HIV risks affecting FSWs in Central Asia.